CAPITAL MARKET EFFICIENCY. AN EMPIRICAL TEST OF THE WEAK-FORM IN THE NIGERIAN CAPITAL MARKET - NWIDOBIE , Barine Michael; ADESINA, Julius Babatunde (Journal of Advanced Studies in Finance, 2014)
The Fama (1970) market-form hypothesis has been subjected to empirical tests in various capital markets worldwide. GARCH analysis of stock prices of twenty sampled firms in April (after earnings announcements) and March (before earnings announcements) from 2007-2013 showed that no stock price volatility exists on earnings announcements evidencing inefficiency of the Nigerian capital market. Improving the efficiency of the Nigerian capital market necessitates the promulgation of investor protection laws requiring improved corporate information dissemination, insiders hoarding privilege information be punished to allow free flow of market information for optimal investor decision making, market transactions and pricing be market driven with security price volatility determined by the interplay of the forces of demand and supply, and detailed corporate non-financial information necessary for decision making in addition to financials should be required to be disclosed by listed firms to improve market efficiency, investor confidence, trading, local and cross-border listings, breadth and depth of the market improving earned income to investors and growth in GDP